Prognostic factors in uterine adenosarcoma: subanalysis of the SARCUT study - Mancari, Rosanna; Yusuf, Yildirim; Macuks, Ronalds; Achimas-Cadariu, Patriciu; Piek, Jurgen Martinus; Sperduti, Isabella; Corrado, Giacomo; Vizza, Enrico; Zapardiel, Ignacio (Frontiers in Oncology, 2024)
The purpose of the study was to analyse the role of prognostic factors on the risk of recurrence and overall survival of patients with uterine adenosarcoma. Methods: A retrospective international multicentre study involving 46 centres collected 32 cases of uterine adenosarcoma were included in the present subanalysis. Clinical and demographics features and tumour characteristics were gathered, as well as information on treatment and relapse. Disease-free and overall survival were analysed. Results: 5-year disease free survival (DFS) was 85.3% and 5-year overall survival (OS) rate was 89.5%. The risk factors that significantly associated with overall survival were age (HR 1.09, 95%CI 1.03-1.15; p=0.004) and FIGO stage II-III (HR 17.75, p=0.002). Patients who experienced early relapse (within 12 months) had a tumour size > 30 mm and advanced stage. The majority of recurred were treated with radiotherapy or surgery and obtained a good response rate. Conclusion: The most significant prognostic factors in uterine adenosarcoma were age and FIGO stage, and indirectly tumour size at diagnosis. The use of secondary surgery and/or radiotherapy could help patients in prolonging free-of-disease status.